Secondary formation of oxygenated and nitrated polycyclic aromatic compounds under stagnant weather conditions: Drivers and seasonal variation - Hao, Weiwei; Liang, Bo; Chen, Jing; Chen, Yang; Wang, Ziqian; Zhao, Xinquan; Peng, Chao; Tian, Mi; Yang, Fumo (The Science of the total environment, 2024)
Severe air pollution tends to occur under stagnant weather conditions. This study focused on the occurrence and formation of PM2.5-bound polycyclic aromatic compounds (PACs) under stagnant weather conditions, in consideration of their adverse human health effect and ecological toxicity. The concentrations of PACs were higher under stagnant weather conditions than in other situations with averaged values of 46.0 ng/m3 versus 12.3–39.9 ng/m3 for total PACs. Secondary formation contributed to over half of the oxygenated and nitrated polycyclic aromatic compounds (OPAHs and NPAHs). Further analyses revealed different formation mechanisms for secondary OPAHs and NPAHs. Secondary production of OPAHs was sensitive to the variations of both temperature (T) and O3 concentration at T < 22 °C but sustained at a high level despite the fluctuation of temperature and O3 concentration at T > 22 °C. Elevated NO2 concentrations favored the formation of inorganic nitrogen-containing products over NPAHs under lower temperature and higher humidity. Stagnant weather events, accompanied by raised PAC levels occurred in all seasons, but their effects on secondary processes differed among seasons. The elevated temperature, lowered humidity, and increased NO2 level facilitated the secondary formation of OPAHs and/or NPAHs during the stagnant weather events in spring and summer. While under the temperature and humidity conditions in autumn and winter, increased NO2 levels during stagnant weather events promoted the production of secondary inorganic nitrogen-containing compounds over organic products. This study raised concern about the toxic organic pollutants in the atmosphere under stagnant weather conditions and revealed different formation mechanisms between secondary oxygenated and nitrated pollutants as well as among different seasons. [Display omitted] •Elevated concentrations of PACs were found under stagnant weather condition.•Secondary formation for PACs was significant under stagnant weather condition.•Secondary production of OPAHs was impacted by both temperature and O3 concentration.•NO2 concentrations played an important role on the secondary formation of NPAHs.•The effect of stagnant weather on secondary formation of PACs differed among seasons.